دراسة إعادة استخدام المياه الرمادية في الأبنية السكنية - دينا الأسطة (Tishreen University, 2019)
يتناول البحث المياه الرمادية,تصنيفها, محتواها, دراسة بعض خواصها الفيزيائية (العكارة - الناقلية), بعض مؤشرات التلوث (pH - BOD5 - COD), دراسة ما تحمله من تلوث بكتيري (F. C وT.C) وذلك في محاولة تجريبية لدراسة هذه المؤشرات على الواقع للمياه الرمادية (دوش - مغسلة) المصرفة من منزل, ودراسة إمكانية إعادة استخدام هذه المياه المصرفة في خزان الطرد للمرحاض الإفرنجي, وما لهذه الدراسة من دور كبير في تقليل هدر المياه, وتوفير الاحتياج المنزلي للمياه، إذ إنْ إعادة استخدام المياه الرمادية بوصفها مورداً بديلاً وغير تقليدي للمياه هو أمر في غاية الأهمية.   This article deals with the greywater, its classifications and content . It also studies physical parameters (turbidity, conductivity), chemical parameters (pH, biological oxygen demand, chemical oxygen demand) and microbiological parameters (fecal coliform, total coliform).   As an experimental trial to study these parameters on the site for indoor waste  greywater (shower, hand wash basins) and the study of the possibility to reuse this waste greywater for toilet flushing.   This study has a great role in saving and reducing the demands of fresh water in house needs, reusing the greywater as an alternative and untraditional source of water is very important issue.